Transgenerational effects of prenatal restricted diet on gene expression and histone modifications in the rat. - Joanna Nowacka-Woszuk; Izabela Szczerbal; Anna M Malinowska; Agata Chmurzynska (PLoS ONE, 2018)
Dietary triggers acting on a developing fetus can affect the functioning of the body in later life; this can be observed on various levels, including epigenetic modifications and gene expression. Early-life programmed changes may be transmitted to successive generations. In this study, the impact of prenatal restricted diet was studied in four generations of rats. We hypothesized that this diet can induce changes in the expression of major genes involved in two epigenetic mechanisms: DNA methylation and histone modifications. The transcript level of six genes involved in these processes (Dnmt1, Dnmt3a, Dnmt3b, Mecp2, Hdac1, and Sin3a) was therefore determined in three tissues (liver, adipose, and muscle). This diet was found to have no effect on the F0 pregnant females. In the F1 progeny (fetuses at day 19 of pregnancy and 4-week-old rats) significant differences in the expression of the genes were observed mostly in the liver; in subsequent generations, we therefore studied only this tissue. Among the genes encoding DNA methyltransferases, significant changes were observed for Dnmt1 in the F1 animals from the restricted group, but these were no longer evident in F2 and F3. The Dnmt3a and Dnmt3b genes showed no differences in mRNA level in F1 fetuses. Concerning the transcript level of the Mecp2 gene only in F1 generation significant changes were found. For the histone modification genes, an increase in the expression of Hdac1 in fetus liver was found in F1 and F2, while its level decreased in F3. The abundance of the Sin3a transcript varied in all generations. It was also found that the mRNA levels of the studied genes correlated highly positive with each other, but only in fetuses from the F1 restricted group. The DNA methylation cell potential, defined as the ratio of SAM (S-adenosylmethionine) to SAH (S-adenosylhomocysteine), was measured in the liver, with no alterations being found in the restricted groups. Evaluation of global histone H3 acetylation showed that it underwent a significant increase in the fetal livers of F1, while during aging (four-week old animals) this difference was no longer maintained. A tendency of increased H3 acetylation in fetuses was also detected in F2 generation. In F1 fetuses from restricted group the increased H3 acetylation positively correlated with transcriptional status of the studied genes. Our results indicate that the prenatal restriction diet can affect the activity of genes involved in epigenetic mechanisms in the liver across generations. Moreover, this feeding type influenced the global histone H3 acetylation in fetal liver.